Comparison of Hip Spica for Duration of 12 Weeks versus 8 Weeks Post-DDH Corrective Surgery in Clinical Outcomes - Maryam , Nida; Orfi , Fayyaz Ahmad; Shah , Qaisar Ali; Yasin, Azhar; Majeed, Hina; Arif , Qamar (Indus Journal of Bioscience Research, 2025)
Objectives: To compare the outcomes of hip spica application for twelve versus eight weeks after performing corrective surgery for developmental dysplasia of hip. Study design: Quasi-experimental study. Place and Duration of the study: Pak-Emirates Military Hospital, Combined Military Hospital, Rawalpindi from April-2024 to February-2025. Methodology: A total of 64 patients who underwent corrective surgery for developmental hip dysplasia were included. Based on duration of hip spica, they were divided into Group-A (12 weeks) and Group-B (8 weeks). Outcomes were compared between groups using clinical (Bhatti & Mckay) and radiological (Severin) scoring systems. Data was analyzed using SPSS version 22. Results: In this study, 64 patients were included divided into two groups. Median age was 17.00 (19.00 – 13.00) months. There were 17 (26.56%) male and 47 (73.44%) female children. Amongst all patients with DDH, 43 (67.19%) had unilateral while 21 (32.81%) had bilateral deformity. There was no statistically significant difference in the clinical outcomes based on BFSS (p = 0.510) and Mckay criteria (p = 0.685) between groups. There was no statistically significant difference in the radiological outcomes based on Severin classification (p = 0.281). Frequency of AVN in Group-A (n = 32) was 12 (37.50%) while in Group-B (n = 32) it was 5 (15.62%), (p = 0.048). Conclusion: Hip spica application for eight weeks should be preferred after performing corrective surgery for developmental dysplasia of hip.